Time and Cost Planning Using the Crashing Method in the Construction of the Nuclear Medicine Building of dr. Soedarso - Arena, Azza; Fitriani, Nurul; Fajry, Raihanny Syafrina; Putra, Septian Eka (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
The construction of the Nuclear Medicine Building of dr. Soedarso is a strategic effort to improve health services in West Kalimantan, especially in dealing with internal diseases such as cancer and heart. This project has an implementation deadline, so effective and efficient planning is required. This research aims to plan project time and costs using the crashing method, as well as consider aspects of human resources (HR), Occupational Health and Safety (K3), and project communication. The methodology used in the preparation of this final project is secondary data analysis in the form of RAB, AHSP, S curve, and basic price in 2024. The calculation of time and cost is carried out based on two approaches to project acceleration, namely the addition of working hours (overtime) and the addition of manpower. The analysis is complemented by the identification of the amount of labor needed, potential hazards at the work site, PPE needs, and communication used in the project. Normally for structural work, this project requires a cost of IDR 8.17 billion with a duration of 84 days. The results of this planning show that the crashing method with the alternative of adding working hours (overtime) costs IDR 8.19 billion, with a duration of 72 days (12 days faster than the normal duration). The crashing method with the alternative of adding labor costs 1DR 8.18 billion, with a duration of 67 days (17 days faster than the normal duration). Based on the results of these calculations, the crashing method can speed up project completion by considering labor productivity and cost-effectiveness. Recommendations from these results can be used as a consideration in making decisions on the implementation of project acceleration by contractors or other project implementing parties.